A new species of Elathous Reitter (Coleoptera: Elateridae) from Turkey - Kabalak, Mahmut; Platia, Giuseppe; Avci, Mustafa (Zootaxa, 2013)
A new click-beetle species, Elathous serti, from Denizli and Isparta provinces of Turkey is described. Photographs of the adults, drawings of the aedeagi, a contrasting comparison table, a key to all Turkish Elathous species, a distribution map, and a table of collecting months and collecting provinces of all Turkish species are provided.